Effects of cobalt-60 gamma on microbial elimination and phytochemical constituents in orthosiphon aristatus (misai kucing) blume (miq.) - Mhd Jamal, Syafiqah; Bahari, Hasnah; Arapoc, Daryl Jesus; Adnan, Muhammad Akif; Mad Diah, Imran Jazary; Jasni, Azmiza Syawani (Penerbit Universiti Kebangsaan Malaysia, 2023)
Medicinal plants are used for various purposes, however, the presence of microorganisms in them is the main safety risk. The study aimed to evaluate the effects of gamma irradiation on microbial contaminants and phytochemical constituents of Orthosiphon aristatus (Blume) Miq. The plant was irradiated using doses of 3, 6, 9, and 12 kGy and the microbial contamination was assessed using phenotypic and genotypic analyses. The qualitative screening using chemical tests was performed to identify the presence of important phytochemical constituents including alkaloids, saponins, flavonoids, tannins, steroids and triterpenes. Results showed that the total microbial counts in O. aristatus were significantly reduced (P < 0.05) following irradiations at 3- and 6 kGy. Pathogenic bacteria were not detected in O. aristatus after irradiation at 6 kGy while the phytochemical constituents were conserved. In conclusion, gamma irradiation has significantly reduced and eliminated microbial contaminants and preserved the phytochemical constituents of O. aristatus. This study highlights the use of a low and specific dose, 6 kGy that is effective to reduce and eliminate microbial contaminants in O. aristatus.